Kontakty społeczności Europy Środkowej i strefy egejskiej w II tysiącleciu p.n.e. Próba analizy archeologiczno-chronometrycznej - Suchowska-Ducke, Paulina (Folia Praehistorica Posnaniensia, 2018)
Long-distance contacts, exchange of goods and more organized forms of trade have been a part of human life since the beginning of what is commonly perceived as culture. One reason for this has always been an unequal geographic distribution of desirable raw materials such as obsidian, flint, or metals. Another driving force comprises the construction of social networks through the exchange of extraordinary objects. My work explores the connectivity and cross-cultural communication between the Bronze Age societies, in particular the Mycenaean world and Central Europe. These links are less researched than those between the Eastern Mediterranean societies of the time. The cultural differences between the Mycenaean Greece and Central Europe, along with the diversity of their societies, provide an interesting and strongly debated case study. There are significant differences in opinions on the nature of these relations, their importance, intensity, and range. Archaeological evidence of cross-cultural contacts between Central Europe and the Aegean is rich and diverse. It includes amber, faience, weapons and tools, dress fasteners, personal ornaments and jewellery, metal vessels, Handmade Barbaric Ware, horse harness made of bone and antlers, loaf-of-bread idols and decorative elements, etc. Despite the often unclear context in which these objects and elements have been found, there is a striking similarity of appearance and this shared materiality may indicate shared notions of technology and ideology.